Digital Innovation Strengthening Community-Centered Health Services through Technology Integration in Romanian Social Welfare Contexts - Asma Elmar Mansurzada; Aytan Azizli; Tofig Hasanov (SocietalServe: Journal of Community Engagement and Services, 2025)
This community engagement program aims to strengthen community-centered health services in Romania by integrating digital innovations into existing social welfare systems. The initiative responds to persistent challenges in accessibility, service coordination, and information flow between local health providers and underserved populations. Through a structured intervention—including digital literacy workshops, development of simple data-collection tools, and collaborative planning sessions with community health workers—the program seeks to enhance local capacity for technology-supported service delivery. A mixed set of participatory and data-driven strategies was employed to ensure that technological solutions align with community needs and institutional capacities. Results indicate significant improvements in digital readiness among participants, increased accuracy of health-service reporting, and stronger collaboration between social welfare actors and community members. Feedback collected from participants highlights a high level of satisfaction with the practicality and relevance of the training sessions. Overall, the program demonstrates that integrating accessible technological innovations into community-based health systems can contribute to more responsive, efficient, and inclusive social welfare structures in Romania. The findings further underscore the importance of continued investment in digital competencies and collaborative governance to support sustainable health-service improvements in socioeconomically diverse contexts.